2007
DOI: 10.1017/s1361491606001894
|View full text |Cite
|
Sign up to set email alerts
|

Was Malthus right? A VAR analysis of economic and demographic interactions in pre-industrial England

Abstract: This paper shows that the interaction between economic and demographic variables in England before the onset of modern economic growth did not fit some crucial assumptions of the Malthusian model. I estimated a vector autoregression for data on fertility, nuptiality, mortality and real wages over the period 1541-1840 applying a well-known identification strategy broadly used in macroeconomics. The results show that endogenous adjustment of population to real wages functioned as Malthus assumed only until the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 37 publications
8
97
4
2
Order By: Relevance
“…A similar strategy was pursued by Nicolini (2007). However, the augmented Dickey-Fuller unit root tests displayed in table 1 caution against the use of a VAR in levels.…”
Section: Var Modelingmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar strategy was pursued by Nicolini (2007). However, the augmented Dickey-Fuller unit root tests displayed in table 1 caution against the use of a VAR in levels.…”
Section: Var Modelingmentioning
confidence: 98%
“…Nicolini (2007) argued that the English demographic (excluding marriages) and real wage series are stationary and concluded a textbook VAR analysis appropriate. The results suggested that the endogenous adjustment of population to real wage fluctuations ceased to exist after 1740, with the positive check eradicated long before the industrial revolution.…”
Section: Demography and The History Of Economic Developmentmentioning
confidence: 99%
“…107-11). For England itself, several studies have found that fertility became less responsive to economic signals around 1750, at the precise period that the English economy began to grow faster and diverge most from other western European economies (Galloway 1988;Nicolini 2007;Crafts and Mills 2009). 10 Demographic responsiveness to economic conditions thus did not depend solely on the EMP and can be observed in some societies in which the EMP did not prevail.…”
Section: Demographic Responsiveness To Economic Conditionsmentioning
confidence: 99%
“…The negative feedback effect of population on real wages has also been found to be weaker than suggested in earlier studies. Nicolini (2007) uses VAR techniques focusing on the short-run relationship between death and birth rates and real wages. For the period from 1541 to 1840, he finds evidence that the real wage-mortality link appeared only up until the 17th century, whereas the real wage-fertility link disappeared before 1740.…”
Section: Related Literature and Our Empirical Approachmentioning
confidence: 99%
“…For the period from 1541 to 1840, he finds evidence that the real wage-mortality link appeared only up until the 17th century, whereas the real wage-fertility link disappeared before 1740. Crafts and Mills (2009) repeat the analysis conducted by Lee and Anderson (2002) and Nicolini (2007), using a new real wage series compiled by Clark (2005). They also come to the conclusion that the Malthusian equilibrium did not exist in late pre-industrial England.…”
Section: Related Literature and Our Empirical Approachmentioning
confidence: 99%